1996
DOI: 10.1111/j.1432-1033.1996.0689r.x
|View full text |Cite
|
Sign up to set email alerts
|

The Enoyl‐[Acyl‐Carrier‐Protein] Reductase (FabI) of Escherichia coli, which Catalyzes a Key Regulatory Step in Fatty Acid Biosynthesis, Accepts NADH and NADPH as Cofactors and is Inhibited by Palmitoyl‐CoA

Abstract: Reduction of enoyl -acyl-carrier-protein (ACP) substrates by enoyl-ACP reductase is a key regulatory step in fatty acid elongation of Escherichia coli. Two enoyl-ACP reductase activities have been described in E. coli, one specific for NADH, the other for NADPH as cofactor. Because of their distinct enzymatic properties, these activities were ascribed to two different proteins. The NADH-dependent enoyl-ACP reductase of E. coli has previously been identified as the FabI protein, which is the target of a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 25 publications
2
124
0
1
Order By: Relevance
“…These data con¢rm that the B. napus cDNA encodes an NADH-speci¢c ENR and in this respect it is unlike the E. coli enzyme that is able to utilise both NADH and NADPH as cofactor [17].…”
Section: Resultsmentioning
confidence: 72%
“…These data con¢rm that the B. napus cDNA encodes an NADH-speci¢c ENR and in this respect it is unlike the E. coli enzyme that is able to utilise both NADH and NADPH as cofactor [17].…”
Section: Resultsmentioning
confidence: 72%
“…Differing fractionations between the enzyme types are therefore plausible. However, E. coli has only 1 of each reductase enzyme (i.e., a single FabG and FabI) yet lipid/water fractionations still vary substantially (23,37,42,43). C. necator has several putative ␤-ketoacyl ACP reductases and FabI-type enoyl ACP reductases (26), but fractionations in C. necator are similar to those of E. coli.…”
Section: Sources Of D/h Variability In Fatty Acidsmentioning
confidence: 99%
“…More recently, isoniazid was shown to prevent radiolabel from being incorporated into the chain extension of C24 -C26 fatty acyl substrates (16 -20), suggesting that the target of isoniazid action is within the mycobacterial FAS-II system. Using a genetic approach to isolate the isoniazid target, a single open reading frame was identified (referred to as inhA) in which transformation of the wild-type gene carried on a multicopy plasmid or allelic exchange with a single amino acid substitution mutant (Ser 94 to Ala) was sufficient to confer isoniazid resistance in Mycobacterium smegmatis (21).The protein encoded by the inhA gene, referred to as InhA, has a similar amino acid sequence to two previously characterized enoyl-ACP reductases, namely FabI from E. coli (28% identity) (22)(23)(24)(25), and ENR 1 from Brassica napus (oilseed rape) (23% identity) (26,27). Further analysis revealed that InhA catalyzes the NADH-dependent reduction of the trans double bond between positions C2 and C3 of fatty acyl substrates (28).…”
mentioning
confidence: 98%
“…The protein encoded by the inhA gene, referred to as InhA, has a similar amino acid sequence to two previously characterized enoyl-ACP reductases, namely FabI from E. coli (28% identity) (22)(23)(24)(25), and ENR 1 from Brassica napus (oilseed rape) (23% identity) (26,27). Further analysis revealed that InhA catalyzes the NADH-dependent reduction of the trans double bond between positions C2 and C3 of fatty acyl substrates (28).…”
mentioning
confidence: 99%